Revitalisasi Halte Transjakarta Bundaran Hi Menjadi Daya Tarik Baru Bagi Warga Jakarta - Rizki Nurul Nugraha; Auliah Nurlizah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Revitalization is a way to revive or reactivate a program or activity. Revitalization at the HI Jakarta roundabout began on April 15 2022 and was completed in November in 2022 with the aim of improving infrastructure and improving services that can increase the number of visitors at Transjakarta shelters. The research conducted with the title Revitalization of the Hi Roundabout Transjakarta Bus Stop Becomes a New Attraction for Jakarta Residents uses a qualitative method which is carried out using data collection techniques by means of interviews and literature studies. The results of the study revealed that with the revitalization at the Bundaran HI Transjakarta bus stop it became a new attraction for visitors who came, but in revitalization there was still a shortage of facilities that were still in the process of being worked on such as escalators, food courts, ATM centers and so on. The revitalization of the Transjakarta bus stop is implemented as a place for photo spots, especially the younger generation with various spots that can be used as photos such as fountains and welcome monument statues, besides that if visitors come at night then visitors can feel Jakarta's city lights. Transjakarta revitalization is also a driving force in the formation of new attractions by covering various strengths and opportunities owned by Transjakarta companies such as strategic locations, friendly service and so on which can be one of the factors in forming new attractions.